University and social development: The required teacher training - Sánchez Raza, Víctor Alexis (2026)
This study was based on the need to update the training and education requirements of teachers in the different faculties of the UCE, which is in line with the demands of 21st-century education. The objective was to analyze the training and education needs of teachers and institution authorities. A descriptive methodology was applied, with a mixed approach (qualitative and quantitative), using a representative random sample by convenience and consecutive sampling, analyzed in ranges and trends, and interpreted with theoretical support, with a historical and sociocultural approach. The research highlighted that teachers need more training in teaching topics, learning methodologies, artificial intelligence in the classroom, critical thinking development, the integration of information and communication technologies, and professional specialization in the subject. In conclusion, the results emphasize the need to develop up-to-date, relevant, and impactful training to strengthen educational quality, with comprehensive training in pedagogical, technological, and professional aspects.